Myxomycetes diversity in Karaman Province forests revealed by moist chamber cultures - Eroğlu, Gönül (Phytotaxa, 2025)
For a biodiversity study of myxomycetes, plant material was collected between 2013 and 2018 in six districts of Karaman Province, Turkey, an area with dense tree populations. Using the moist chamber technique, 617 myxomycete samples developed from 1076 samples of plant material. From these samples, 87 myxomycete taxa belonging to 26 genera were identified. The high species diversity in the area can be interpreted as being linked to the variety of substrates. Perichaena depressa was the most commonly detected species in the study and developed on almost all substrates. Information regarding species diversity, preferred substrates, and ecological importance of myxomycetes in Karaman Province is provided within the article.